(untitled) (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2013)
Introduction. The feature of ranging positioning techniques is the required true coordinates selection. It leads to the need of finding the unique solution of the analytical problem. The results of the study. The newness of the method is coordinate determination based on Saybel‘s direction finder operation and value processing of signal power in reception points. Conclusions. The method allows to increase the efficiency of objects control providing invariance of the reception points topology and decreasing the control blunders because of the coordinates definition ambiguity